Lesson Study dan Booklet Tanaman Obat Simalungun: Strategi Inovatif dalam Meningkatkan Hasil Belajar IPA - Purba, Ika Rosenta; Saragih, Marlindoaman; Huda, Muhammad Komarul; Damanik, Ali Akbar (Journal of Natural Sciences, 2025)
Globalization and modernization are the causes of the degradation of local wisdom, including knowledge of traditional medicinal plants. This study aims to integrate local wisdom of Simalungun medicinal plants in science learning to improve student learning outcomes. The method used is Classroom Action Research in two cycles, each consisting of the Plan, Do, See stages. Data were collected through pretest and posttest tests and observations of learning implementation. The results showed an increase in the average pretest score from 57.83 to 77.83 in cycle I, and from 66.08 to 80.43 in cycle II, with classical completeness increasing from 60.87% to 82.60%. Changes in learning strategies through heterogeneous grouping and the use of concrete media contributed to students' conceptual understanding. The conclusion of this study confirms that learning that integrates local wisdom-based media in a reflective and collaborative framework can encourage significant and contextual improvements in learning outcomes.